Pre-operative proteinuria, postoperative acute kidney injury and mortality: A systematic review and meta-analysis. Issue 7 (July 2021) - Chang, Chun-Yu; Chien, Yung-Jiun; Kao, Ming-Chang; Lin, Han-Yu; Chen, Yu-Long; Wu, Meng-Yu
Abstract : OBJECTIVE: To investigate the association of pre-operative proteinuria with postoperative acute kidney injury (AKI) development as well as the requirement for a renal replacement therapy (RRT) and mortality at short-term and long-term follow-up. BACKGROUND: Postoperative AKI is associated with surgical morbidity and mortality. Pre-operative proteinuria is potentially a risk factor for postoperative AKI and mortality. However, the results in literature are conflicting. METHODS: We searched PubMed, Embase, Scopus, Web of Science and Cochrane Library from the inception through to 3 June 2020. Observational cohort studies investigating the association of pre-operative proteinuria with postoperative AKI development, requirement for RRT, and all-cause mortality at short-term and long-term follow-up were considered eligible. Using inverse variance method with a random-effects model, the pooled effect estimates and 95% confidence interval (CI) were calculated. RESULTS: Twenty-eight studies were included. Pre-operative proteinuria was associated with postoperative AKI development [odds ratio (OR) 1.74, 95% CI, 1.45 to 2.09], in-hospital RRT (OR 1.70, 95% CI, 1.25 to 2.32), requirement for RRT at long-term follow-up [hazard ratio (HR) 3.72, 95% CI, 2.03 to 6.82], and long-term all-cause mortality (hazard ratio 1.50, 95% CI, 1.30 to 1.73). In the subgroup analysis, pre-operative proteinuria was associated with increased odds of postoperative AKI in both cardiovascular (OR 1.77, 95% CI, 1.47 to 2.14) and noncardiovascular surgery (OR 1.63, 95% CI, 1.01 to 2.63). Moreover, there is a stepwise increase in OR of postoperative AKI development when the quantity of proteinuria increases from trace to 3+. CONCLUSION: Pre-operative proteinuria is significantly associated with postoperative AKI and long-term mortality. Pre-operative anaesthetic assessment should take into account the presence of proteinuria to identify high-risk patients. PROSPERO REGISTRATION: CRD42020190065. Abstract : Supplemental Digital Content is available in the text